2006
DOI: 10.1002/ajhb.20527
|View full text |Cite
|
Sign up to set email alerts
|

Common set of genes regulates low‐density lipoprotein size and obesity‐related factors in Alaskan Eskimos: Results from the GOCADAN Study

Abstract: Increasing incidence of cardiovascular disease in traditionally low-risk Alaskan Eskimos is a cause for concern. The purpose of this study was to examine the genetic and environmental correlations of low-density lipoprotein (LDL) subfractions with obesity-related factors in Alaskan Eskimos, using data from the first 954 participants of the Genetics of Coronary Artery Disease in Alaska Natives Study. Estimates of genetic and environmental influence were calculated using a maximum likelihood variance component m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 39 publications
(44 reference statements)
2
11
0
Order By: Relevance
“…Second, the observed peaks are adjacent to the region containing QTL for several obesity-related anthropometric traits found the GOCADAN study (Voruganti et al ., 2011). This observation is consistent with another set of data from the GOCADAN population (Voruganti et al ., 2006) which suggests that cholesterol phenotypes and obesity-related factors have shared genetic determinants in Alaska Native people. Future studies of putative genetic associations with these phenotypes should account for such pleiotropic effects to improve estimate validity and precision (Park et al ., 2011).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Second, the observed peaks are adjacent to the region containing QTL for several obesity-related anthropometric traits found the GOCADAN study (Voruganti et al ., 2011). This observation is consistent with another set of data from the GOCADAN population (Voruganti et al ., 2006) which suggests that cholesterol phenotypes and obesity-related factors have shared genetic determinants in Alaska Native people. Future studies of putative genetic associations with these phenotypes should account for such pleiotropic effects to improve estimate validity and precision (Park et al ., 2011).…”
Section: Discussionsupporting
confidence: 93%
“…A recent large-scale meta-analysis of genome-wide association studies (Winkler et al ., 2012) has identified a locus in that gene as a sex-specific determinant of obesity-related traits like the waist-to-hip ratio, showing a robust association in women but not men. Given that women in Arctic communities have some of the highest visceral obesity rates in the world (Risica et al ., 2000; Voruganti et al ., 2006), MACROD1/LRP16 variation in this population may be an important contributor to health outcomes. Additionally, MACROD1/LRP16 has been shown to activate nuclear factor κB (Wu et al ., 2011), a key inflammatory component of the pathogenesis of atherosclerosis (Kutuk and Basaga, 2003) that can be influenced by environmental factors such as dietary cholesterol or statin therapy (Jasinska et al ., 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Study size was derived from previous studies of genetic effects on complex diseases in Mexican American,30,31 American Indian,32,33 and Alaskan Eskimo34,35 extended families. The GKDZI sample size was similar to these studies, in which we obtained significant heritabilities.…”
Section: Methodsmentioning
confidence: 99%
“…Analyses conducted in the same Alaskan Eskimo population found that subclasses of low density lipoproteins (LDL) have significant genetic correlations with parameters of adiposity (Voruganti et al, 2006). Small and medium LDL had positive genetic correlations with body weight, BMI and skinfolds.…”
Section: Discussionmentioning
confidence: 99%